Celebrity activism on racial justice during COVID-19: the death of George Floyd, the rise of Naomi Osaka, and the celebritization of race in pandemic times. Issue 1 (2nd January 2022) - Deflem, Mathieu
ABSTRACT: This paper examines the development of celebrity activism on racial justice in the United States during the COVID-19 pandemic. Extending from efforts to provide support in relief efforts, celebrity activism during the first year of the pandemic dramatically turned to matters of racial justice in the wake of the video-taped police killing of George Floyd. Based on a constructionist perspective of celebrity, I analyze the patterns and dynamics of this celebrity activism regarding racial justice in terms of the motives and objectives on the part of the celebrities and the reception thereof by the public and in the media. I will thereby focus on the activism of Naomi Osaka as a particularly successful effort because the tennis star's advocacy on racial justice has enabled her to acquire a central position in the world of celebrity activism. I show that the racial justice activism embraced widely among celebrities during the COVID-19 pandemic developed in function of the dynamics of celebrity culture rather than as an exponent of contemporary racial justice currents. Racial justice itself thereby became an object of celebrity culture, the widespread and enduring nature of which both scholars and advocates of racial justice today need to recognize.